Menuju Sistem e-Goverment Terpadu dan Handal Berbasis Cloud Computing - Didik Widianto, Eko (Jurnal Sistem Komputer, 2011)
Traditional and centric approach which use dedicated server to host e-Goverment applications makes the cost of the solution becoming high, under-utilized computing resources (inefficiency) and cannot fulfill requirements to deliver fourth level deployment ofe-Government, regarding to its integrated services,reliability, interoperability and availability. This research provides a framework to implement cloud computing for integrated and reliable e-Government system. Cloud model has been developed. Its implementation platform using open source software are also identified. Finally, further research to realize this community-type of cloud is challenged.